2010
DOI: 10.1088/0067-0049/189/2/270
|View full text |Cite
|
Sign up to set email alerts
|

The Multiwavelength Survey by Yale–chile (Musyc): Deep Medium-Band Optical Imaging and High-Quality 32-Band Photometric Redshifts in the Ecdf-S

Abstract: We present deep optical 18-medium-band photometry from the Subaru telescope over the ∼30 × 30 Extended Chandra Deep Field-South, as part of the Multiwavelength Survey by Yale-Chile (MUSYC). This field has a wealth of ground-and space-based ancillary data, and contains the GOODS-South field and the Hubble Ultra Deep Field. We combine the Subaru imaging with existing UBVRIzJHK and Spitzer IRAC images to create a uniform catalog. Detecting sources in the MUSYC "BVR" image we find ∼40,000 galaxies with R AB < 25.3… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
364
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 278 publications
(376 citation statements)
references
References 66 publications
11
364
1
Order By: Relevance
“…Using a likelihood ratio technique (Ciliegi et al 2003), the optical/infrared counterparts of the radio sources have been identified (Bonzini et al 2012). Excluding the outermost region as defined in Bonzini et al (2012), the wealth of multi-wavelength data available for the E-CDFS allows robust estimates of photometric redshifts (Santini et al 2009;Taylor et al 2009;Cardamone et al 2010;Rafferty et al 2011). The area with photometric redshifts coverage includes 779 radio sources that will constitute our main sample for the analysis presented in this paper.…”
Section: Radio Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Using a likelihood ratio technique (Ciliegi et al 2003), the optical/infrared counterparts of the radio sources have been identified (Bonzini et al 2012). Excluding the outermost region as defined in Bonzini et al (2012), the wealth of multi-wavelength data available for the E-CDFS allows robust estimates of photometric redshifts (Santini et al 2009;Taylor et al 2009;Cardamone et al 2010;Rafferty et al 2011). The area with photometric redshifts coverage includes 779 radio sources that will constitute our main sample for the analysis presented in this paper.…”
Section: Radio Datamentioning
confidence: 99%
“…The UV-NIR photometry is obtained combining the BVR selected Cardamone et al (2010) catalogue, the K selected Taylor et al (2009) (Dickinson & FIDEL Team 2007). A likelihood ratio technique (Ciliegi et al 2003) followed by a careful visual inspection has been used to reconstruct the optical-to-MIR photometry of the radio sources (see Bonzini et al 2013, for details).…”
Section: Fir Luminosity Of Radio Sourcesmentioning
confidence: 99%
“…These data will be made available as part of the overall SERVS public release. Observations are concentrated on longer optical and near-IR wavebands, as these are generally more useful for photometric redshift estimates at higher redshifts (van Dokkum et al 2006;Brammer et al 2008;Ilbert et al 2009;Cardamone et al 2010). In the optical, the SDSS filter set is used where possible, as the narrower bands allow higher-fidelity photometric redshifts than the Johnson-Cousins system (see Fig.…”
Section: Further Ground-based Data Taken or To Be Taken By The Servs mentioning
confidence: 99%
“…The five SERVS fields are centered on, or close to, those of corresponding fields surveyed by the shallower Spitzer Wide-area Infrared Extragalactic Survey (SWIRE; Lonsdale et al 2003), and they overlap with several other major surveys covering wavelengths from the X-ray to the radio. Of particular importance is near-infrared data, as these allow accurate photometric redshifts to be obtained for high redshifts (van Dokkum et al 2006;Brammer et al 2008;Ilbert et al 2009;Cardamone et al 2010): SERVS overlaps exactly with the 12 deg 2 of the VISTA Deep Extragalactic Observations (VISTA VIDEO; Jarvis et al 2012, in preparation) survey (Z, Y , J, H, and K s bands) in the south and is covered by the UKIRT Infrared Deep Sky Survey (UKIDSS; Lawrence et al 2007) survey (J, K) in the north. SERVS also has good overlap with the Herschel Multitiered Extragalactic Survey (HerMES; Oliver et al 2012) in the far-infrared, which covers the SWIRE and other Spitzer survey fields, with deeper subfields within many of the SERVS fields.…”
Section: Introductionmentioning
confidence: 99%
“…The power of multiwavelength photometric observations to recover galaxy redshifts has been known since the late fifties (Baum 1957), and it has been confirmed in the past decade with deep blank-field imaging surveys (e.g., Ilbert et al 2009;Cardamone et al 2010;Dahlen et al 2013;Rafelski et al 2015). Although spectroscopic redshifts are much better in precision than photometric estimates, photometry has two important advantages with respect to spectra: the number of sources that can be observed at the same time, and sensitivity.…”
Section: Introductionmentioning
confidence: 99%